Reproduction in Punganur cattle - BRAMHAIAH, K VEERA; RAO, S T VIROJI; REDDY, Y RAVINDRA (The Indian Journal of Animal Reproduction, 2003)
Reproductive performance over a period of 5 years of Punganur cattle was analysed. The data revealed that the performance of Punganur cattle is as good as other dual purpose cattle and is comparable with the other Indian breeds. The parameters recorded were age at puberty 827.86 ± 48.15 days, body weight at puberty 109.00 ± 3.51 Kgs, age at first calving 1240.14 ± 89.87 days, postpartum service period 152.00 ± 14.50 days, number of services per conception 1.57 ± 0.07, gestation period 284.04 ± 0.83 days and inter calving period 473.46 ± 18.13 days, respectively.